Pengaruh Current Ratio Dan Gross Profit Margin Terhadap Laba Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia - Novi Lestari; Alvina (Jurnal Ekonomi dan Bisnis, 2021)
This study focuses on The Effect of Current Ratio and Gross Profit Margin on Profits in Manufacturing Companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange aims to determine the effect of Current ratio on profits in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange, the effect of Gross Profit Margins on profits in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange and to determine the effect of the Current Ratio and Gross Profit Margin on profits in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange.